Strategi Pembelajaran Kerjasama Tim Pada Pemasangan Peranca di Portside Model Mooring And Windlass STIMARYO - Ade Chandra Kusuma; Iswanto Iswanto (Majalah Ilmiah Bahari Jogja, 2021)
The implementation of role-playing learning in the installation of peranca is a contextual learning model in the process of knowledge transfer to achieve the competence of cadets at the Yogyakarta Maritime High School or Stimaryo as prospective workers on board. Leadership and teamwork are carried out in the mooring and windlass anchor machine model belonging to Stimaryo in the Nautical Studies Study Program. The purpose of this paper is classroom action research in the process of attainment in the form of completeness in achieving minimum competency or completeness criteria of at least 75. The second marine skills learning method uses the role play method or role play prepared by the lecturer or instructor in the form of learning scenarios. This learning scenario has indicators in the form of competency achievement and teamwork ability for cadets level II in the third semester of the Nautical Studies Study Program at the Yogyakarta Maritime College in learning Marine Skills II in the Mooring and Windlass media belonging to the Yogyakarta Maritime College. The results achieved are the formation of a professional workforce, especially the ability of team collaboration, especially the deck department in the shipping sector, especially the Nautical Studies Study Program.